The Effect of Social Support on Academic Burnout of Final Year Students of the Undergraduate Nursing Study Program at Harapan Bangsa University - Rina Nur Aeni; Indri Heri Susanti; Adiratna Sekar Siwi (PROMOTOR, 2023)
Student burnout can lead to feelings of helplessness, loss of attention or avoidance of the learning environment, and dropping out of dreams. This condition can occur due to excessive workload or continuous academic demands. This creates stress and negatively impacts mental health. This study aims to determine how social support impacts the academic boredom of undergraduate nursing study program students at Harapan Bangsa University. This study conducted correlation descriptive research using a cross-sectional approach. The total sampling involved 84 students. To measure social support, Interpersonal Support Evaluation List (ISEL) scale questionnaires and academic boredom were used. with the Maslach Burnout Inventory-Student Survey (MBI-SS) questionnaire. For analysis, the Spearman rank test is used. The results showed that students experienced academic burnout. The final level of the Nursing Study Program The Bachelor Program at Harapan Bangsa University is the most dominant with the medium category (67.9%). Social support for final-year students of the Undergraduate Nursing Study Program at Harapan Bangsa University is the most dominant in the medium category (65.5%). The conclusion is that there is a relationship with p value 0.009 (p < 0.05), the level of academic fatigue of Nursing students of the Undergraduate Program of Universitas Harapan Bangsa.